2019
DOI: 10.3390/ijerph16245072
|View full text |Cite
|
Sign up to set email alerts
|

Tourists’ Thermal Experience and Health in a Commercial Pedestrianized Block: A Case Study in a Hot and Humid Region of Southern China

Abstract: With the development of the economy in China, the tourism industry has become a form of daily entertainment for citizens. Commercial pedestrianized blocks have been designed as recreational centers for tourists, serving as outdoor public space and scenic spots. The use of these regions is directly determined by the outdoor thermal environment. So far, few studies have been conducted on tourists’ thermal experience in commercial pedestrianized blocks, especially in the hot and humid region of southern China. Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…In accordance with previous studies, people's thermal comfort in the outdoor environment will be affected by different urban design parameters including aspect ratio (H/W, H is the average height of the building and the W is the width of the street), sky view factor (SVF), street orientation, urban vegetation and paving material of ground surface. The aspect ratio (H/W) expresses the ratio between the average height of the building and the street width [4], several studies [5][6][7] have shown that increasing building average height (aspect ratio), impeding solar radiation and providing shading can contribute to ameliorate the thermal environment. The second factor is the sky view factor (SVF), which is expressed as "the ratio of the sky which can be seen from a stable position on a surface to that potentially available" [8], this index is a number ranging from 0 to 1.…”
Section: Introductionmentioning
confidence: 99%
“…In accordance with previous studies, people's thermal comfort in the outdoor environment will be affected by different urban design parameters including aspect ratio (H/W, H is the average height of the building and the W is the width of the street), sky view factor (SVF), street orientation, urban vegetation and paving material of ground surface. The aspect ratio (H/W) expresses the ratio between the average height of the building and the street width [4], several studies [5][6][7] have shown that increasing building average height (aspect ratio), impeding solar radiation and providing shading can contribute to ameliorate the thermal environment. The second factor is the sky view factor (SVF), which is expressed as "the ratio of the sky which can be seen from a stable position on a surface to that potentially available" [8], this index is a number ranging from 0 to 1.…”
Section: Introductionmentioning
confidence: 99%